Convolutive neural network-based approaches to video image analysis - LIN ZHENQUAN (International Journal of Multidisciplinary Research and Studies, 2023)
The focus of this research is on providing a foundational understanding of convolutional neural networks for its application, in particular, to the detection of moving objects. Furthermore, the paper details the functioning and interplay of convolutional layers. Manually analysing a huge dataset of video stills is now the only viable option, but this is time-consuming and requires human expertise. The algorithms included into neural networks allow for autonomous analysis and identification.